(untitled) (Fiep Bulletin - online, 2013)
Take care of children from an early age is important to ensure the health of the population. Combating overweight and obesity is a way of preventing diseases. The research was to examine the prevalence of overweight and obesity of children duly registered in the municipal Network of Bananal-SC, during the period February to May 2012 with the child’s age from 7 to 10 years who attend the public education in Guaramirim. The focus of the field research was verify that these children would be overweight and obesity calculated through BMI and subscapular skinfold triciptal and. The calculation of BMI was conducted by the Division of body weight in kilograms by the square of height in meters. Cutting limits for the definition of overweight and obesity were = 85 ? p ? 97, obesity = p ? 97 (2007 WHO). We studied a total of 252 children, 116 (46.05%) male and 136 (53.95%) females. The first sample showed a prevalence of 14.3% (36 students) were overweight and 13.9% (35 students) presenting with obesity. In the second sampling applications with the activities described were obtained improved results, where we obtained 13.8% overweight and 12.7% obese. While the values ??are small, the work made ??a difference for these children. The prevalence of overweight were comparable to those found in some regions of Brazil.Whereas the percentages were worrying realized awareness work with families, suggesting changing menu with accompanying nutritionist and targeted physical work. The school developed research in various disciplines and lectures on the topic.